2022
DOI: 10.1103/physrevlett.129.145501
|View full text |Cite
|
Sign up to set email alerts
|

Many-Body Correlations Are Non-negligible in Both Fragile and Strong Glassformers

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…We note that S(0) is a primary measure of how fluid "structure" relates to its thermodynamic state and figures prominently in some models of glass formation, such as the mode-coupling theory. [39][40][41][42][43] We make some tentative suggestions for why some thermodynamic properties exhibit thermodynamic scaling, while this scaling property does not hold for other properties that might be expected to exhibit this property based on an assumed effective power-law intermolecular interaction potential. Thermodynamic scaling then offers some hints about the extraordinary interrelationships between the thermodynamics and dynamics of GF liquids.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…We note that S(0) is a primary measure of how fluid "structure" relates to its thermodynamic state and figures prominently in some models of glass formation, such as the mode-coupling theory. [39][40][41][42][43] We make some tentative suggestions for why some thermodynamic properties exhibit thermodynamic scaling, while this scaling property does not hold for other properties that might be expected to exhibit this property based on an assumed effective power-law intermolecular interaction potential. Thermodynamic scaling then offers some hints about the extraordinary interrelationships between the thermodynamics and dynamics of GF liquids.…”
Section: Introductionmentioning
confidence: 87%
“…Recent works have established the inadequacy of some more modern structurally based models of liquid dynamics, such as the mode-coupling theory, and other theories emphasizing the pair correlation function or averages of this quantity, providing molecular insights into the more abstract reasoning of Goldstein’s energy landscape arguments. Parenthetically, we note that there are recent promising works to include information about higher-order density correlations into a mode-coupling framework, which appears to lead to a much improved agreement between predictions and simulations, but historically the fluid structure has often been identified with the readily observable pair correlation function or its Fourier transform, the static structure factor. Later, Goldstein suggested that the configurational entropy might occupy a place of primacy in this type of relationship after the development of the Adam–Gibbs (AG) model of glass formation, and he first formulated his highly influential energy landscape view of the dynamics of GF liquids as an elaboration of this reasoning .…”
Section: Introductionmentioning
confidence: 96%
“…On the other hand, other properties, such as the low angle scattering intensity S (0) and G ∞ / k B T , do not exhibit thermodynamic scaling, where S (0) is related to the isothermal compressibility κ T , density ρ, and T through the definition, S (0) = ρ k B T κ T , appropriate in general for materials in equilibrium. We note that S (0) is a primary measure of how fluid “structure” relates to its thermodynamic state and figures prominently in some models of glass formation, such as the mode-coupling theory. We make some tentative suggestions for why some thermodynamic properties exhibit thermodynamic scaling, while this scaling property does not hold for other properties that might be expected to exhibit this property based on an assumed effective power-law intermolecular interaction potential. Thermodynamic scaling then offers some hints about the extraordinary interrelationships between the thermodynamics and dynamics of GF liquids …”
Section: Introductionmentioning
confidence: 89%
“…for monodisperse systems where, following convention, we omit the superscript for the two-body structure factor and denote by . Although the convolution approximation for is usually assumed to be reasonable for systems with relatively weak attracting interaction potentials ( 46 ), a recent mode-coupling theory study has revealed that including can qualitatively change the glass transition diagram even for simple hard-sphere mixtures ( 54 ). Moreover, the convolution approximation provides even less accuracy for systems such as silica ( 46 ).…”
Section: Theory Of Liquid Structurementioning
confidence: 99%